Design and implementation of QoS differential service scheme based on 4/5G converged network - Zhu Jialin; Zhang Min; Li Kai; Liu Xin; Zhang Liwei (Dianzi Jishu Yingyong, 2022)
With the deployment and commercialization of 5G networks, providing differentiated services for different users in the existing network has become a research hotspot in the industry based on the different needs of the business for network capabilities. Therefore, this paper proposes a method to realize the converged deployment and unified invocation of 4/5G network quality of service(QoS) differentiated services. This scheme includes the network architecture of 4/5G network QoS differentiated service fusion deployment, the method of QoS platform server to terminal 4/5G user automatic identification, and the end-to-end process of 4/5G converged QoS service. The design of this scheme enables the third party to directly call the QoS capability of the operator using the unified scheduling interface of the whole country without distinguishing the 4/5G form of the user, giving full play to the network advantages and value of the operator.